2016
DOI: 10.1002/prep.201500211
|View full text |Cite
|
Sign up to set email alerts
|

Demolition Mechanism and Behavior of Shaped Charge with Reactive Liner

Abstract: 1IntroductionReactive materials areaclass ofs olid energetic materials that are formulatedt orelease energy under highly dynamic loads. In general, they are formed by introducing active metal powders into ap olymer binder, typically such as PTFE, and then consolidatedb yapress/sinterp rocess. Remarkably different from traditional energeticm aterials,t hey have features of high mechanical strength and sufficient insensitivity so as not to sustain ad eflagration reaction using traditional initiationt echniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…The typical device of the static explosion test for the penetration performance of jet into the metal target plate is usually composed of a shaped charge, a support tube controlling the stand-off distance and several metal blocks with specific materials and thickness. This method has been widely used by scholars [28][29][30]. The test device configuration diagram in this paper is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The typical device of the static explosion test for the penetration performance of jet into the metal target plate is usually composed of a shaped charge, a support tube controlling the stand-off distance and several metal blocks with specific materials and thickness. This method has been widely used by scholars [28][29][30]. The test device configuration diagram in this paper is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Their numerical and empirical models showed that the increase in concrete strength led to a significant decrease in the shaped charge jet penetration depth. Xiao et al [18] investigated the damage effects of the reactive liner shaped charge on the multi-layered targets. By pressing and sintering, three types of reactive liners made of a mixture of Al/PTFE powders were fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing to traditional high explosives, Al-PTFE has higher energy density, higher strength and better workability. Al-PTFE is suitable for multiple applications such as impact projectile, anti-missile weapon, high explosive countermeasure, biological agent defeat and underwater explosion [1][2][3].…”
Section: Introductionmentioning
confidence: 99%